2016
DOI: 10.1186/s12874-016-0167-6
|View full text |Cite
|
Sign up to set email alerts
|

Minimal important differences for fatigue patient reported outcome measures—a systematic review

Abstract: BackgroundFatigue is the most frequent symptom reported by patients with chronic illnesses. As a subjective experience, fatigue is commonly assessed with patient-reported outcome measures (PROMs). Currently, there are more than 40 generic and disease-specific PROMs for assessing fatigue in use today. The interpretation of changes in PROM scores may be enhanced by estimates of the so-called minimal important difference (MID). MIDs are not fixed attributes of PROMs but rather vary in relation to estimation metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
107
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(122 citation statements)
references
References 61 publications
10
107
1
4
Order By: Relevance
“…However, literature regarding the vitality domain specifically has shown that the MCID can vary widely amongst health states and is generally set at a 5 point difference in scores. 44,45 So, while statistically significant, our results may not reflect a clinically meaningful decrease in the patient’s vitality.…”
Section: Discussionmentioning
confidence: 55%
“…However, literature regarding the vitality domain specifically has shown that the MCID can vary widely amongst health states and is generally set at a 5 point difference in scores. 44,45 So, while statistically significant, our results may not reflect a clinically meaningful decrease in the patient’s vitality.…”
Section: Discussionmentioning
confidence: 55%
“…For example, the group‐level MID of 5.3 points means that this is the minimal difference between treatment groups that would be clinically significant. A direct comparison cannot be drawn because they are different measures, but for context a T‐score MID range of 3.0–5.0 was reported for PROMIS Fatigue‐7 . Because of the small group of patients who were “a little better,” this value is exploratory, and we recommend future studies to establish MID cut‐points for other interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Non-white ethnicity was associated with a 2.95 lower initial fatigue severity and a reduction in fatigue severity of 1.60 points each year. In addition, a one-point increase in haemoglobin was predictive of a small, but not clinically meaningful (Nordin et al, 2016), increase in fatigue severity of .02 each year (B = À0.05, p = .050, 95% CI À0.10, À0.00008). In addition, a one-point increase in haemoglobin was predictive of a small, but not clinically meaningful (Nordin et al, 2016), increase in fatigue severity of .02 each year (B = À0.05, p = .050, 95% CI À0.10, À0.00008).…”
Section: Predictors Of Fatigue Severity Over Timementioning
confidence: 95%
“…In the final model, including all the predictor variables (N = 14), only ethnicity was a significant predictor of the initial level of fatigue severity (B = À2.95, p = .024, 95% CI À5.51 to À0.40) and change in fatigue severity (B = 1.36, p = .009, 95% CI 0.35 to 2.36). These coefficients represent clinically significant changes in fatigue severity on the CFQ, particularly taking into consideration the additive impact of ethnicity over time (Nordin et al, 2016). These coefficients represent clinically significant changes in fatigue severity on the CFQ, particularly taking into consideration the additive impact of ethnicity over time (Nordin et al, 2016).…”
Section: Predictors Of Fatigue Severity Over Timementioning
confidence: 99%